Urban planning in MOROCCO: realities and challenges: The model of emerging urban centers in the TADLA region - AITKHADJOU, Youssef; DABARHI, Abdelghani (Journal of Humanities & Social Sciences, 2021)
The evocation of the context of urban planning policy in Morocco, from pre-colonization until now, shows that it has accumulated an important legal arsenal which has reflected on the Moroccan urban sphere, by orienting some of its components such as the installation of the inhabitant activities, as well as by affecting the tools and methods adopted in town planning.The colonial period introduced Morocco into a phase of rapid urbanization compatible with the new production model and the new distribution of urban centers; however, it affected negatively the life of the population. These conditions abruptly persisted during the period of independence despite attempts to remedy them through plans and experiments.Through this article, we aim to follow the most important changes in urban planning policy in Morocco and try to assess the effectiveness of this policy through the model of emerging urban centers in the TADLA region.
Keywords: urban planning; planning design; emerging urban centers; urban rehabilitation; Tadla region